Weakly Nearly Prime Submodules - Sabah Sadiaq, Ali; K. Mohammadali, Haibat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this article, unless otherwise established, all rings are commutative with identity and all modules are unitary left R-module. We offer this concept of WN-prime as new generalization of weakly prime submodules. Some basic properties of weakly nearly prime submodules are given. Many characterizations, examples of this concept are stablished.